SAT0477 Rituximab Treatment for Connective Tissue Disease Associated Interstitial Lung Disease: A Retrospective Case Series. (9th June 2015) - Carter, S.; Jutley, G.; Kiely, D.; Condliffe, R.; Renshaw, S.; Whyte, M.; Kuet, K.; Kilding, R.; Akil, M.
Abstract : Background: Interstitial lung disease (ILD) is a common cause of morbidity and mortality in connective tissue disease (CTD) (1), particularly in systemic sclerosis, where it is the most common cause of death (2). Despite several immunosuppressive regimes, including intravenous cyclophosphamide, a significant proportion of patients have progressive ILD. Recent evidence has shown that rituximab is an effective treatment in antisynthetase syndrome associated ILD (3) and in treatment refractory connective tissue disease associated interstitial lung disease (CTD-ILD) as rescue therapy (4). Objectives: The objective of this study was to investigate patient outcomes when using rituximab for CTD-ILD refractory to standard immunosuppression, in our specialist centre in Sheffield, UK. Methods: A retrospective case review was performed on 12 patients who had received rituximab for CTD-ILD. Details of previous treatment, pulmonary function tests, imaging, autoimmune profiles and basic demographic data were collected. Exercise tolerance, symptoms of dyspnoea and percent predicted forced vital capacity (FVC) and percent predicted diffusion capacity of carbon monoxide (DLco) were compared from baseline and six to nine months after receiving rituximab, to assess response to treatment. Results: After six months treatment four patients had significant increases in FVC or DLco defined as an increase of ≥10% or ≥15% from baseline respectively, and three patients had stable disease. Five patients showed progressive disease including one patient with diffuse systemic sclerosis who died and one patient with polymyositis who required lung transplantation. A steroid sparing effect was observed, with a median reduction in prednisolone dose of 5mg daily at six months. Conclusions: We found that rituximab can be an effective treatment in some patients with progressive CTD-ILD, even in disease refractory to standard treatment with IV cyclophosphamide. Patients with Jo-1 polymyositis were more likely to have a significant response to treatment. Further randomized controlled studies are needed to aid treatment decisions in this patient group to enable clinicians to identify likely responders, to determine if rituximab is as effective as cyclophosphamide and if use in early CTD-ILD will improve patient outcomes. References: Castelino FV et al. Interstitial lung disease in connective tissue diseases: evolving concepts of pathogenesis and management. Arthritis Research and Therapy. 2010;12(4):213. Tyndall AJ et al. Causes and risk factors for death in systemic sclerosis: a study from the EULAR Scleroderma Trials and Research (EUSTAR) database. Annals of the rheumatic diseases. 2010 Oct;69(10):1809-15. Sem M et al. Rituximab treatment of the anti-synthetase syndrome: a retrospective case series. Rheumatology. 2009 Aug;48(8):968-71. Keir GJ et al. Severe interstitial lung disease in connective tissue disease: rituximab as rescue therapy. The European respiratory journal. 2012 Sep; 40(3):641-8. Disclosure of Interest: None declared